Why Synthetic Fuels Are Necessary in Future Energy Systems - Wilson, I. A. Grant; Styring, Peter (Frontiers in Energy Research, 2017)
We propose a hypothesis that fuels will continue to be critical elements of future energy systems. The reasons behind this are explored, such as the immense benefits conferred by fuels from their low cost of storage, transport and handling, and especially in the management of the seasonal swing in heating demand for a country with a summer and winter season such as the UK. Empirical time-series data from Great Britain are used to examine the seasonal nature of the demand for liquid fuels, natural gas and electricity, with the aid of a daily Shared Axis Energy Diagram. The logic of the continued need of fuels is examined, and the advantages and disadvantages of synthetic fuels are considered in comparison to fossil fuels.